CLINICAL COURSE OF CONGENITAL HEART DEFECTS IN NEWBORNS WHO HAVE EXPERIENCED INTRAUTERINE HYPOXIA - Yuldasheva G.G; Badieva D.S (Western European Studies, 2024)
This article presents the results of an analysis of the characteristics of the course of congenital heart disease in newborns who have suffered intrauterine hypoxia. It has been established that in 100% of children with organic heart pathology and in 95% of children with the syndrome of maladaptation of the cardiovascular system, the presence of perinatal infection is detected in the maternal history, which is clinically manifested by signs of persistent pulmonary hypertension and the functioning of fetal communications, fluid retention, hepatomegaly, and a decrease in diastolic arterial blood pressure. pressure. In the first year of life, cases of acute respiratory viral infections and pneumonia are often recorded
Keywords: congenital heart defects; clinical course; perinatal infections